Izbira Sodnega sveta - Fajdiga, Mohor (Zbornik znanstvenih razprav (Pravna fakulteta. 1991), 2021)
Recruitment in the judiciary is currently a particularly hot topic in Europe. In Slovenia, the Judicial Council, as a guarantor of judicial independence having a central role in the appointment procedure, is supposed to ensure the selection of the most competent candidates. However, the selection process fails to be transparent and the reasoning of the choice is insufficient and unconvincing. Therefore, the author first outlines the Slovenian courts’ response to such decision-making of the Judicial Council. Restrained judicial review based on trust in the discretionary choice by the Judicial Council has become established in case law. Therefore, the contribution assesses the Slovenian legal framework in light of the latest European standards: the right to efficient judicial protection and to a tribunal established by law from Article 6 of the European Convention on Human Rights and Article 19 of the Treaty of EU. Especially, the inadequate reasoning of decisions and the fact that the Judicial Council does not write a record of the consultation in violation of the applicable legislation turns to be problematic.
Keywords: evropski standardi; pravna država; Slovenija; sodišča; sodni svet; sodniki; zakonodaja